Faith and Reason: An Inquiry into the Concept of Faith in Kierkegaard’s Fear and Trembling - Yohanes Kukuh Cahyawicaksana; Yohanes Fery (Asosiasi Ahli Filsafat Keilahian Indonesia, 2022)
Faith is often accused of being irrational and considered lower than reason because it is not objective and universal. In other words, at a practical level, believers cannot always obey God’s commands communicated in their inwardness. However, they must always be subject to the demands of a universal and objective reason. This elaboration attempts to counter this assumption departing from the description that Kierkegaard presented in his work, Fear and Trembling. There, Kierkegaard states that a single individual believer is higher than the ethical-rational demands that bind him. In other words, the purpose of this text is to show that faith has its rationality and is not subject to reason. Therefore, through the textual analysis method of Kierkegaard’s Fear and Trembling, this paper would like to analyze the constitutive elements of faith, how they work, and why faith is not subject to ratio. The point of view used in this elaboration is Kierkegaardian subjectivity. The analysis finds that the constitutive elements of faith are anxiety, courage, passion, the strength of the absurd, and hope (as components of faith), which need to be carried out with a double movement of faith.